PUBLIC SERVICE DELIVERY AND JOINT-UP GOVERNANCE AS CHALLENGES OF THE NOTION GOOD GOVERNANCE IN INDONESIA: BRINGING THE PEOPLE BACK IN - Riswanda Riswanda (Jurnal Administrasi Publik, 2010)
This essay simply argues that the idea of the so-called ‘good governance’ should bring the public back in. In other words, it is vital to take into account the interests, needs and wants of all stakeholders related to whatever efforts taken by governments to cope with public issues. For the Indonesian government, in particular, the essay points out a major issue, such as public service delivery, as challenges for the notion good governance, good corporate governance or suchlike to be paid more attention to. To critically measure public service delivery by referring to what, why how, to what extent and in whose opinions the measurement criteria come from is vital as well. The objective of this essay is to contribute to the discourse on how to better see the notion of good governance in Indonesia. This study is questioning to what extent the notion can be put into practice to measure quality of service delivery. This study comes up with the idea of networked governance as a more sophisticated way rather than just keep promoting the notion which may create, to use Frederickson phrase, ‘governance, governance everywhere…substantively the same as already established perspectives in public administration, although in a different language’.